2006
DOI: 10.1136/ard.2006.054734
|View full text |Cite
|
Sign up to set email alerts
|

Resistin in rheumatoid arthritis synovial tissue, synovial fluid and serum

Abstract: Background: Resistin is a newly identified adipocytokine which has demonstrated links between obesity and insulin resistance in rodents. In humans, proinflammatory properties of resistin are superior to its insulin resistance-inducing effects. Objectives: To assess resistin expression in synovial tissues, serum and synovial fluid from patients with rheumatoid arthritis, osteoarthritis and spondylarthropathies (SpA), and to study its relationship with inflammatory status and rheumatoid arthritis disease activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
176
0
8

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 235 publications
(194 citation statements)
references
References 27 publications
10
176
0
8
Order By: Relevance
“…These authors observed an association of synovial fluid resistin with inflammatory markers of the disease. Moreover, the association between serum resistin levels, disease activity, and acute phase reactants, including C-reactive protein and IL-1Ra antagonizing IL-1β, suggests that resistin may be a significant mediator in the inflammatory process of RA [31,101]. On the contrary, serum resistin levels were comparable between patients with erosive and non-erosive hand osteoarthritis and were neither associated with signs of clinical nor laboratory markers of inflammation [102].…”
Section: Resistin In Rheumatic Diseasesmentioning
confidence: 95%
See 2 more Smart Citations
“…These authors observed an association of synovial fluid resistin with inflammatory markers of the disease. Moreover, the association between serum resistin levels, disease activity, and acute phase reactants, including C-reactive protein and IL-1Ra antagonizing IL-1β, suggests that resistin may be a significant mediator in the inflammatory process of RA [31,101]. On the contrary, serum resistin levels were comparable between patients with erosive and non-erosive hand osteoarthritis and were neither associated with signs of clinical nor laboratory markers of inflammation [102].…”
Section: Resistin In Rheumatic Diseasesmentioning
confidence: 95%
“…In contrast to mice, only a low level of expression of resistin has been found in mature adipocytes in humans [24][25][26][27]. In humans, resistin is highly expressed in the bone marrow compared to other tissues [28], but it is also present in trophoblastic cells of placenta, pancreas, primary cell leukemia, synovial fluid, synovial tissue, and circulating blood [22,24,[28][29][30][31][32][33][34]. The particular cells that express resistin in white adipose tissue are monocytes and macrophages [26,28,35].…”
Section: Sites Of Resistin Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are demonstrations that resistin may also be involved in the pathogenesis of RA: resistin has been found in the plasma and the synovial fluid of RA patients, and injection of resistin into mice joints induces an arthritis-like condition, with leukocyte infiltration of synovial tissues, hypertrophy of the synovial layer, and pannus formation (Bokarewa et al 2005, Senolt et al 2007). However, plasma resistin levels in RA patients appear similar to those found in healthy controls and although in some studies of RA patients resistin levels were higher in synovial fluid than in serum (which shows that circulating levels of adipokines do not necessarily reflect the situation in the joint), the discrepancy may be due simply to the increased permeability of inflamed synovial membrane (Otero et al 2006, Schaffler et al 2003, Bokarewa et al 2005.…”
Section: Resistinmentioning
confidence: 99%
“…Previous studies have investigated the function of resistin in mouse obesity and diabetes models, and have implicated resistin in the pathogenesis of obesity-mediated insulin resistance and type 2 diabetes (3,12,13). Moreover, it has been reported that resistin is closely associated with inflammation (14)(15)(16). Resistin regulates the synthesis and secretion of proinflammatory cytokines such as tumor necrosis factor α (TNF-α), interleukin-6 (IL-6) and IL-1β in macrophages via a nuclear factor κB (NF-κB)-dependent pathway (17)(18)(19)(20), but the specific receptor of resistin in vivo has not yet been identified.…”
Section: Introductionmentioning
confidence: 99%